Evaluation of sleep quality in high-risk pregnant women admitted to a public maternity hospital (Research, Society and Development, 2024)
Objectives: To evaluate sleep quality in high-risk pregnant women admitted to hospital. Methodology: This is an observational, cross-sectional and analytical study. The quantitative methods were carried out in a public maternity hospital of reference for high complexity in Teresina-PI. Non-probabilistic, intentional and convenience sampling was carried out and the Pittsburgh index was applied. Results: The results showed that 23 pregnant women had good sleep quality and 7 had poor sleep quality. The results regarding the sociodemographic characteristics of the pregnant women showed that the prevalent age group was over 35 years old (36.7%), 53.3% of the pregnant women had completed secondary school, 30% had not completed secondary school and 13.3% had completed higher education, the highest prevalence among pregnant women in the survey was for women who had had up to three pregnancies (80%), followed by multiparous pregnant women (20%), who had had more than three pregnancies. The most frequently listed discomfort at bedtime was lower back pain. Conclusion: It was concluded that the quality of sleep in hospitalized high-risk pregnant women is quite good, although there are significant associations such as increased abdominal volume negatively affecting maternal sleep patterns.